Biomedical Applications: Multilayered Blood Capillary Analogs in Biodegradable Hydrogels for In Vitro Drug Permeability Assays (Adv. Funct. Mater. 14/2013). (4th April 2013) - Yoshida, Hiroaki; Matsusaki, Michiya; Akashi, Mitsuru
<x xml:space="preserve">Abstract</x> Multilayered blood capillary analogs are constructed in biodegradable hydrogels as reported by Mitsuru Akashi and co‐workers on page 1736. The size, orientation, length, layer, and cell type of the artificial blood capillaries are easily controlled. Additionally, permeability control of serum albumin by altering blood vessel cell layers is demonstrated. This technique will be useful as an innovative technology for drug permeability assessment to human blood vessels. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>